Letters of Farman Fatehpuri to Syed Moeenur Rahman - Sabahat Saad Moeen; Noreena Tahreem Babar (بازیافت)
In Rakmah's article, linguist-researcher. Critic - lexicographer and educationist Dr. Farman Fatehpuri with a brief introduction, 12 letters with footnotes are included. These letters are named after the educationist, researcher, editor and expert of Ghalibyat Dr. Syed Moeenur Rahman. These letters are in the family of Dr. SyedMoeenur Rahman. It will be correct to say that Dr. Farman Fathpuri and Dr. Syed Moeenur Rahman's long-standing relationship is 40 years old. Along with academic and literary topics, personal relationships are also written in the letters. This article will help the readers to understand the entire literary situation of the era of literature. Key Words: Farman Fatehpuri, Syed Moeenur Rahman, Urdu letters, literary topics.